Laser patterning of transparent polymers assisted by plasmon excitation - Elashnikov, R; Trelin, A; Otta, J; Fitl, P; Mares, D; Jerabek, V; Svorcik, V; Lyutakov, O (Soft matter, 2018)
Plasmon-assisted lithography of thin transparent polymer films, based on polymer mass-redistribution under plasmon excitation, is presented. The plasmon-supported structures were prepared by thermal annealing of thin Ag films sputtered on glass or glass/graphene substrates. Thin films of polymethylmethacrylate, polystyrene and polylactic acid were then spin-coated on the created plasmon-supported structures. Subsequent laser beam writing, at the wavelength corresponding to the position of plasmon absorption, leads to mass redistribution and patterning of the thin polymer films. The prepared structures were characterized using UV-Vis spectroscopy and confocal and AFM microscopy. The shape of the prepared structures was found to be strongly dependent on the substrate type. The mechanism leading to polymer patterning was examined and attributed to the plasmon-heating. The proposed method makes it possible to create different patterns in polymer films without the need for wet technological stages, powerful light sources or a change in the polymer optical properties.